1984
DOI: 10.1063/1.447800
|View full text |Cite
|
Sign up to set email alerts
|

1 B 2u↔1A1g spectroscopy of jet-cooled benzene: Single vibronic level fluorescence studies

Abstract: As part of an investigation of intramolecular energy transfer in jet-cooled 1B2u benzene, an extensive study of one photon 1B2u↔1A1g spectroscopy has been carried out. Our data lead to an assignment for ν8 in the 1B2u state (1516 cm−1), to a number of new assignments involving activity in ν18 and ν4, and they show that many of the higher vibrational levels in the 1B2u manifold are mixed. The activities of components of combination levels with different vibrational angular momenta have been observed and used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 29 publications
3
71
1
Order By: Relevance
“…Both sets of the total OOS values are lower than the other theoretical values, the results of Bernhardsson et al [40] being within the reported error bars for both sets of experimental results [46,47] while our results are within only one of the experimental results of Pantos et al [46]. While both sets of calculations roughly agree on the contributions of the ν 7 and ν 9 inducing modes, our calculations indicate a larger contribution from the ν 8 than the calculations of Bernhardsson et al [40] and the measurements of Callomon [44] and Stephenson et al [45].…”
Section: A Benzene C 6 Hcontrasting
confidence: 39%
See 1 more Smart Citation
“…Both sets of the total OOS values are lower than the other theoretical values, the results of Bernhardsson et al [40] being within the reported error bars for both sets of experimental results [46,47] while our results are within only one of the experimental results of Pantos et al [46]. While both sets of calculations roughly agree on the contributions of the ν 7 and ν 9 inducing modes, our calculations indicate a larger contribution from the ν 8 than the calculations of Bernhardsson et al [40] and the measurements of Callomon [44] and Stephenson et al [45].…”
Section: A Benzene C 6 Hcontrasting
confidence: 39%
“…The other vibronic modes, from the ν 7 , ν 8 and ν 9 inducing modes, are not as easily identified in the optical spectra as the mode ν 6 and, as expected, Table I shows some discrepancy concerning the relative intensities of the experimental results. In particular, the experimental results of Callomon [44] do not report any contribution from the ν 8 mode, and the measurement of Stephenson et al [45] shows a contribution of 0.6%. Table I shows that, except for the results of Ziegler and Albrecht [20] and Metz et al [42], the other theoretical and experimental results agree that the inducing ν 6 mode is responsible for about 90% of the total OOS of these vibronic bands.…”
Section: A Benzene C 6 Hmentioning
confidence: 92%
“…26 All the transitions can be readily assigned, as they are on average shifted in frequency by +30 cm À1 with respect to the corresponding gas phase transitions. 27 The broad features in the spectrum originate from benzene molecules present in the detection chamber as background gas. The contribution of these benzene molecules to the spectrum has been reduced in several ways.…”
Section: Resultsmentioning
confidence: 99%
“…Following the first experiments reporting ultrafast non-radiative decay in the "channel 3" region by Callomon et al 1 , rotationally resolved spectra 4,8,9,11,20,23,28 revealed that, for a given vibrational state, the lifetimes were strongly-dependent on the rotational quantum number. Below "channel 3", experiments by Rice and coworkers showed that the rate of ISC as a function of excess energy was fairly random; 14,24 however, if the rate of ISC was plotted as a function of the number of quanta in a particular vibrational mode, a monotonic increase in the rate of ISC was observed.…”
Section: Introductionmentioning
confidence: 99%